Analysis of Biomechanical Properties of the Lumbar Extensor Myofascia in Elderly Patients with Chronic Low Back Pain and That in Healthy People. (18th February 2020) - Wu, Zugui; Zhu, Yue; Xu, Wu; Liang, Junquan; Guan, Yingxin; Xu, Xuemeng
Abstract : There is limited research on the changes of biomechanical characteristics of the lumbar extensor myofascia in elderly patients with chronic low back pain. This study aimed to compare the biomechanical properties of the lumbar extensor myofascia in elderly patients with chronic low back pain and healthy people when resting and to analyze the relationship between the Japanese Orthopedic Association (JOA) score, visual analog scale (VAS) score, Cobb angle, and disease course and the biomechanical characteristics of the lumbar extensor myofascia. This case-control study included 40 elderly patients with chronic low back pain and 40 healthy volunteers. MyotonPRO was used to measure the biomechanical properties of the bilateral lumbar extensor myofascia (at L3/L4 level) in all participants, and the reliability of the MyotonPRO test was measured. Cobb angle was measured from lumbar computed tomography or magnetic resonance imaging data. JOA and VAS scores were used to evaluate lumbar function and pain. We found that muscle tone, stiffness, and elasticity of the left and right lumbar extensor myofascia in patients with chronic low back pain were very reliable among different operators. The average lumbar extensor muscle tone and stiffness were significantly higher in patients with chronic low back pain than those in healthy controls. The average elasticity of the lumbar extensor myofascia of patients with chronic low back pain was significantly lower than that of the healthy controls. The JOA score was negatively correlated, while the VAS score was positively correlated with the mean values of tone, stiffness, and elasticity of the bilateral lumbar extensor myofascia (logarithmic decrement). Disease course had no significant correlation with muscle tone, stiffness, and elasticity of the lumbar extensor myofascia. No significant correlation was found between Cobb angle and muscle tone, stiffness, and elasticity of the lumbar extensor myofascia in either group.